PERAN BAZNAS DALAM PEMBANGUNAN USAHA MIKRO DI KOTA MOJOKERTO - Syai'in; Sukamto, Akhmad (Irtifaq, 2020)
Abstract: This article discusses the role of BAZNAS in the development of micro businesses in Mojokerto. Using a qualitative approach in the form of field research, the writers collect data by observation, interviews, and documentation with the procedure of datra analysis of data reduction analysis, data presentation, and drawing conclusions. The results of the study show that the role of BAZNAS of Mojokerto in the development of micro businesses, the small and medium business operators are helped by the sharia business financing program (i.e. PUSYAR) provided by the Mojokerto BAZNAS. Small and medium businesses can be helped in developing their businesses because BAZNAS provides maximum services and cooperates with the Sharia Economic Community to foster UMKM entrepreneurs of Mojokerto's superior products in business management, supervision and marketing based on sharia. Keywords: BAZNAZ, Micro Business